Clinical predictors for favorable outcomes from endovascular recanalization in wake-up stroke. (July 2017) - Sung, Sang Min; Lee, Tae Hong; Cho, Han Jin; Cho, Gi Yong; Jung, Dae Soo; Lee, Jae Il; Ko, Jun Kyeung; Yip, Samuel
Highlights: The purpose of this study was to evaluate clinical predictors of outcomes from endovascular recanalization in WUS patients. This study focuses on the time intervals between last-seen-normal and recanalization in wake up stroke as a predictor for functional outcome. Rates of recanalization and symptomatic intracranial hemorrhage in our study were comparable with previous endovascular studies. Our study shows that symptom recognition-to-door time (SRDT) is an independent predictor of both an improvement of NIHSS score and a good functional outcome in endovascular recanalization for WUS patients. Our study suggest that the effort should be laid on interventions to decrease the SRDT for achieving an improvement of the NIHSS score and a good functional outcome after endovascular recanalization in WUS. Even though the sample size is relatively small, our study reinforces the concept of "time is brain" in WUS patients. Abstract: Background and purpose: Patients who have acute stroke symptoms present on awakening are ineligible for standard intravenous thrombolysis due to the unclear onset time of symptoms. Some of these wake-up stroke (WUS) patients may benefit from endovascular recanalization. This study aimed to evaluate clinical predictors of outcomes from endovascular recanalization in WUS patients. Methods: Forty-one WUS patients with internal carotid (ICA) or middle cerebral artery (MCA) occlusion treated with endovascular recanalization were reviewed. Regression analysis was performed to measure clinical predictors of outcomes from endovascular recanalization in WUS patients. Results: The mean initial NIHSS score was 16.41 ± 4.96 (5–24). The mean symptom recognition-to-door time (SRDT) was 108.85 ± 65.80 (19–230) min. Successful recanalization (TICI 2b-3) was achieved in 29 patients (70.7%). Thirty-four patients improved on NIHSS (amount 7.59 ± 4.84, range; 1–17) at 7 days after recanalization. At 90 days after recanalization, a mRS of ≤2 was achieved in 19 patients (46.3%) and a mRS of ≤3 was achieved in 24 patients (58.5%). No symptomatic intracerebral hemorrhage occurred. Multivariate regression analysis identified SRDT ( P  = 0.019), successful recanalization ( P  = 0.005), and hypertension ( P  = 0.013) were factors associated with an improvement of the NIHSS score. For a good functional outcome at 90 days, SRDT ( P  = 0.036) and initial NIHSS score ( P  = 0.016) were found to be significant predictors. Conclusions: The results of this study suggest that the SRDT is an independent predictor of both an improvement of NIHSS score and a good functional outcome in endovascular recanalization for WUS patients.